Combination of Superselective Arterial Embolization and Radiofrequency Ablation for the Treatment of a Giant Renal Angiomyolipoma Complicated with Caval Thrombus. (11th May 2016) - Stamatiou, Konstantinos N.; Moschouris, Hippocrates; Marmaridou, Kiriaki; Kiltenis, Michail; Kladis-Kalentzis, Konstantinos; Malagari, Katerina
Abstract : This is a case of a 78-year-old male patient with multiple angiomyolipomas of a solitary right kidney. The largest of these tumors (maximum diameter: 13.4 cm) caused significant extrinsic compression of the inferior vena cava complicated by thrombosis of this vessel. Treatment of thrombosis with anticoagulants had been ineffective and the patient had experienced a bleeding episode from the largest right renal angiomyolipoma, which had been treated by transarterial embolization in another institution, 4 months prior to our intervention. Our approach included superselective transarterial embolization of the dominant, right kidney angiomyolipoma with hydrogel microspheres, which was combined, 20 days later, with ultrasonographically guided radiofrequency ablation. Both interventions were uneventful. Computed tomography 2 months after ablation showed a 53% reduction in tumor volume, reduced space-occupying effect on inferior vena cava, and resolution of caval thrombus. Nine months after intervention the patient has had no recurrence of thrombosis or hemorrhage and no tumor regrowth has been observed. The combination of superselective transarterial embolization and radiofrequency ablation seems to be a feasible, safe, and efficient treatment of large renal angiomyolipomas.